ANALISIS PELAKSANAAN EVALUASI UNTUK MENINGKATKAN MUTU PEMBELAJARAN BIOLOGI DI SEKOLAH - Novi Indah Lestari; Abdul Razak; Lufri Lufri; Zulyusri Zulyusri (Bioilmi: Jurnal Pendidikan, 2022)
In the learning process the teacher does not only transfer knowledge but must have academic qualifications in accordance with his field. Good learning planning is the key to achieving the expected learning objectives. The purpose of this study to analyze the implementation of the evaluation of Biology learning in schools. This research method is a meta-analysis by examining data sources originating from national or international journals published in the last five years (2017-2021). This research begins with formulating the topics to be studied and then formulating the problems. The next stage collecting relevant articles to collect data. The data was obtained from searching online journals through Google Scholar. The topic used are "Analysis of the Implementation of the Evaluation and Improvement of the Quality of Learning Biology". From the search results there are 30 articles. Data were obtained and re-analyzed using quantitative methods. Based on the results of the analysis of the implementation of the evaluation of biology learning with the proven ability to improve the quality of Biology Learning in schools with significant results after being given treatment, namely 74.59% compared to the results before being given treatment, namely 63.95%, increasing by 10.63%. So with Evaluation it can describe the quality of learning that has been planned and can provide input on the learning program being carried out.